Bacterial evasion of antimicrobial peptides by biofilm formation - Otto, M (Current topics in microbiology and immunology, 2006)
Biofilm formation is a main virulence determinant in many bacterial infections. It significantly increases bacterial resistance to antibiotics and innate host defense. In general, the specific physiology of biofilms and the barrier function of the extracellular biofilm matrix determine resistance to antibacterials. However, resistance to antimicrobial peptides appears to be mainly based on the interaction with biofilm and capsule exopolymers. These polymers may work by electrostatic repulsion and/or sequestration of antibacterial substances. As biofilm polymers play an eminent role in biofilm structuring and resistance, their destruction by dedicated enzymes is a promising attempt to prevent colonization and develop treatment for biofilm-associated infections.